1999
DOI: 10.1159/000017124
|View full text |Cite
|
Sign up to set email alerts
|

Agraphia in Alzheimer’s Disease

Abstract: Writing disorders are an early manifestation of Alzheimer’s disease (AD), often more severe than language difficulties. AD patients produce shorter and less informative written descriptions of a complex picture than controls. These abbreviated texts also include many intrusions, semantic substitutions, and misspellings. Syntactic difficulties are characterized by a reduction of subordinate clauses rather than by the occurrence of grammatical errors. Lexical spelling is systematically more impaired and affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
3
26
1
Order By: Relevance
“…Our patients showed visuoconstructional errors even in the early stages of disease, which is inconsistent with the findings of a previous study (Croisile, 1999). In that study, Croisile suggested that visuospatially disorganized handwriting appears later than linguistic abnormalities in the progression of the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Our patients showed visuoconstructional errors even in the early stages of disease, which is inconsistent with the findings of a previous study (Croisile, 1999). In that study, Croisile suggested that visuospatially disorganized handwriting appears later than linguistic abnormalities in the progression of the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…These results agree with previous research in which slower reading speed than in healthy controls has been reported in mild AD patients [11,22]. The corresponding reduction in handwriting speed was of 59%, which agrees with data from an earlier study [14]. Since no errors were observed in performance of reading and handwriting tasks, differences between groups were interpreted as the consequence of the progressive psychomotor decline related to aging.…”
Section: Healthy Elderlysupporting
confidence: 92%
“…While parietal lobe atrophy was also present in the patients with typical AD, it was much less severe than that observed in the PCA patients, and in contrast it seemed to affect the left parietal lobe greater than the right. Features such as agraphia, acalculia and apraxia typically result from left parietal lobe damage, and are relatively common findings in patients with typical AD [12,39,51].…”
Section: Discussionmentioning
confidence: 99%